Property Rights and the Regulatory State. Issue 2 (August 2019) - Vraciu, Cosmin
Abstract: When state regulations prevent owners from certain uses of their property, is this action of the state a taking of property which requires compensation? One way of answering this problem, within a framework viewing property as a bundle of rights, is to inquire into whether the incident of use is an essential element of the bundle making up the property. Given the difficulties with figuring out what is essential and what is not, I propose an alternative solution, which does not give up the bundle-of-rights framework, but which, while assuming all incidents to be equally essential, it concentrates, instead, upon the legal entitlements conveying those incidents. I begin by arguing that while the incident of possession may be expressed by a right to exclude, the incident of use is expressed by a Hohfeldian liberty, and then I consider the consequences of this argument for the question of regulatory takings. I argue that while the liberty to use does not render the incident of use meaningless (at least, insofar as regulation of property use is concerned), there is nonetheless a significant distinction between transgressing a right and transgressing a liberty, and this implies that what it takes for an infringement of the right to exclude to be translated into a taking of the (whole) property is less than what it takes for the infringement of the liberty to use to be translated into a taking of property. As I show in the paper, we can achieve this result either by means of an argument from 'constitutional residue' or by means of an argument from the specification of constitutional rights.